SISTEM PAKAR DIAGNOSA VIRUS KOMPUTER BERBASIS WEB (Information Technology and Telematics, 2013)
Abstract - Computer viruses can damage (eg by corrupting the data on the document), make computer users feel annoyed, or no effect at all. System development methods used in this study is   an   expert   system that consists of the identification, conceptualization, formalization, implementation,   evaluation and  development system.  System design  using  the  Levelled DFD context diagram and consists of a Level 0 DFD and ERD. Creating  a  website  using   PHP  programming  and  MySQL database.. Keywords – Expert System, Computer Virus Komputer,  PHP, MySQL